Assessment of Spiritual Vitality and Marital Satisfaction in Parents of Children Aged 6–12 Years with Autism Spectrum Disorder - Davoudnia , Fereshteh; Ordoo, Fatemeh (Psychological Research in Individuals with Exceptional Needs, 2026)
The aim of this study was to investigate the relationship between spiritual vitality and marital satisfaction among parents of children aged 6–12 years diagnosed with Autism Spectrum Disorder (ASD). This study employed a descriptive-correlational design with a quantitative approach. The statistical population consisted of parents referring to the Iranian Autism Association in Tehran Province, from whom 100 participants (50 couples) were selected using purposive sampling. Data were collected using the standardized Afrouz Marital Satisfaction Questionnaire and the Afrouz Spiritual Vitality Scale. Data analysis was conducted through correlation coefficients and analysis of variance using SPSS software. The findings indicated that there was no significant relationship between the total score of spiritual vitality and marital satisfaction among the parents. However, subscale analyses revealed that certain dimensions of marital satisfaction, including marital contentment, positive thinking, and communicational-social behaviors, were correlated with spiritual vitality, and the relationships among these components were statistically significant. In addition, no significant differences were observed between fathers and mothers regarding spiritual vitality and marital satisfaction; nevertheless, the mean scores reflected relatively low to moderate levels of these two variables among the parents. These findings suggest that although spiritual vitality alone is not a direct predictor of marital satisfaction in this group, fostering spirituality-oriented dimensions within married life may indirectly influence the quality of the relationship among couples raising a child with autism. The results highlight the necessity of designing holistic interventions focused on strengthening spiritual and communicational resources in these families.